Community Forests of Rogho and Boala, Significant Carbon Sinks in the Center-West Region of Burkina Faso - Yanogo, Pawendkisgou Isidore; Tiamiyu, Kasimou (European Scientific Journal, ESJ, 2023)
This study aimed to evaluate the carbon stock potential of the community forests of Rogho and Boala. The indirect method was adopted to estimate the above and below-ground woody biomass, while the integral collection method was chosen to estimate the herbaceous biomass. Data was collected from 77 circular plots with a radius of 18m, which included the diameter and height of plant species within these plots. The data analysis that the Boala community forest produced 2,150.7 t/ha of biomass, which corresponded to 1,075.35 t/ha of carbon, while the Rogho community forest produced 402.81 t/ha of biomass, which corresponded to 201.41 t/ha of carbon. The G1 group had the highest amount of carbon sequestered with 2,327.61 t/ha of biomass, which corresponded to 1,163.80 tC/ha. The CCEN unit had the lowest amount with 262.49 t/ha of biomass, which corresponded to 131.24 tC/ha. The proportion of herbaceous biomass in the carbon stock in the Rogho and Boala sites was 4.49% and 0.8%, respectively. Therefore, there is a need to strengthen the management of these forest areas to further improve their carbon storage potential.